Kriptografi Hibrida Cipher Block Chaining (CBC) dan Merkle-Hellman Knapsack untuk Pengamanan Pesan Teks - Novianti, Chofifah Alfin; Khudzaifah, Muhammad; Jauhari, Mohammad Nafie (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2023)
A secret message is a message that can only be seen by those who are entitled. In its delivery, a procedure is needed to keep the secret message secure, which is called cryptography. This research uses hybrid cryptography Cipher Block Chaining (CBC) and Merkle-Hellman Knapsack. The purpose of this research is to find out the encryption and decryption process of hybrid cryptography Cipher Block Chaining (CBC) and Merkle-Hellman Knapsack. The stages in this research use a qualitative approach with the library research method. In the encryption process with CBC, plaintext is encrypted first and the result called ciphertext. Furthermore, the key and Initialization Vector (IV) from CBC are encrypted using Merkle-Hellman Knapsack by generating a public key first and producing cipherkey. In the decryption process cipherkey is first decrypted using Merkle-Hellman Knapsack by calculating the inverse modulo . The decryption process continues by decrypting ciphertext using CBC. The result of securing messages using hybrid cryptography Cipher Block Chaining (CBC) and Merkle-Hellman Knapsack has a higher level of security than using only one cryptographic algorithm. As for the future, this research can be used to expand knowledge about securing text messages using hybrid cryptography algorithm CBC and Merkle-Hellman Knapsack.